2020
DOI: 10.1007/s00399-020-00734-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias in patients with SARS-CoV‑2 infection and effects of the lockdown on invasive rhythmological therapy

Abstract: Background Since the outbreak of the coronavirus disease 2019 (COVID-19) pandemic, various strategies have been taken worldwide to reduce the risk of infection. As part of the amendment to the Infection Protection Act, elective medical interventions were restricted, leading to a change in patient care. However, the consequences of the lockdown on the treatment of rhythmological patients in Germany remains unclear. Objectives The aim of this study was to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…This result reflects the impact of the pandemic on programmed interventions in arrhythmology and strengthens prior reports that the recommendation to limit hospital admissions to the ER, combined with the fear of patients being infected in the hospital, had an impact on urgent/emergent admissions and interventions. The same phenomenon seems to have occurred in other countries that adopted similar measures 6–8 . Compared to the homologous period of 2019, we also noted patients who came to the ER during “lockdown” were significantly more likely to be on statins and had a tendency for being treated more frequently with a RAAS inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…This result reflects the impact of the pandemic on programmed interventions in arrhythmology and strengthens prior reports that the recommendation to limit hospital admissions to the ER, combined with the fear of patients being infected in the hospital, had an impact on urgent/emergent admissions and interventions. The same phenomenon seems to have occurred in other countries that adopted similar measures 6–8 . Compared to the homologous period of 2019, we also noted patients who came to the ER during “lockdown” were significantly more likely to be on statins and had a tendency for being treated more frequently with a RAAS inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…Catalonia has reported an overall decrease of 56.5% in pacemaker and ICD implantations during the first wave of COVID-19, affecting both elective and urgent implantations, while a study from England also showed decreases in pacemaker, CRT, and ICD implantations for both elective and urgent indications during the first lockdown [ 8 , 12 ]. Peru reported a decrease of 73% in de novo pacemaker implantations for all aetiologies after the beginning of their first social isolation period, and in Germany a decrease of 18% in pacemaker implantations was recorded during their first lockdown [ 7 , 9 ]. Our study also revealed lower daily rates; however, when comparing the changes using rate ratios, we found more significant changes during the second lockdown compared with the first.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that this was also the case in Denmark, even though it has been less severely affected by COVID-19 than Italy [ [3] , [4] , [5] ]. In addition, countries including Greece, Peru, England, and Germany experienced a reduced number of implantations of cardiac implantable electronic devices (CIEDs) during the pandemic [ [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%